Chemical composition and anti-irritant capacity of whole body extracts of Ulomoides dermestoides (coleoptera, tenebrionidae) - MENDOZA MEZA, Dary Luz; SAAVEDRA A., Stephanie (Vitae, 2013)
Background: In traditional medicine of Central and South America, the tenebrionid beetle Ulomoides dermestoides is used as an a phrodisiac, for the treatment of inflammatory diseases and cancer. Recently was reported cytotoxic and genotoxic properties of non-polar extract of U. dermestoides; also anti-inflammatory and immunomodulatory activity of aqueous whole body extract of beetle was reported, it suggests the existence of components with potential pharmacology use. On the other hand, it is necessary to identify those polar and non-polar extracts of U. dermestoides with anti-irritant properties for the membranes and blood vessels, which will be used in subsequence biological test and clinical assays. Objectives: The purpose of this research was to identify the chemical composition of methanolic and hexanic extracts of U. dermestoides, and to assess their anti-irritant capacity. Methods: The extracts were obtained from adult beetles of U. dermestoides. The chemical composition of the extracts was determined by gas chromatography-mass spectrometry (GC-MS) and the anti-irritant effect of each extract was evaluated by means of a modified assay of irritation of the chorioallantoic membrane (CAM) of fertilized chicken eggs (HET-CAM); theresults were expressed as irritation index (IR). Results: Six common compounds were identified in both extracts: limonene, myristic, palmitic, estearic, oleic, and linoleic fatty acids. But in the alone methanolic extract were found: 1-pentadecanol, alpha-pinene, beta-phellandrene and alpha-terpinene, whereas in thehexanic extract were found: 2-methyl-p-benzoquinone, 2,4-dihidroxy-1-ethylbenzene, 2,5-dimethylquinone, saturated and unsaturated hydrocarbons and alcohols. The methanolic extract of U. dermestoides showed potential anti-irritant effect in the HET-CAM test (IR = 3.09 ± 0.11), similar to that observed with Nimesulida (IR = 2.05 ± 0.14), a non-steroid anti-inflammatory drug (NSAID) used as positive control for irritation inhibition reaction. The hexanic extract did not show anti-irritant capacity. Conclusions: The results demonstrated the anti-irritant effect of the methanolic extracts of U. dermestoides that could be attributed to compounds with anti-inflammatory activity as oleic acid and limonene.